IMITATION OF THE STEAM TREATMENT OF RESERVOIRS ON THE HIGH-VISCOSITY OIL FIELDS - Смоловик, Ліліана Романівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The article presents analysis of the outcomes obtained from the imitation of the steam treatment of reservoirs on the high-viscosity oil fields. The article considers different conditions of oil occurrence and different options of wells layout. It also also investigates the temperature effect and water flow rate for discharge pumping and pressure distribution in the working tank.